Prioritising time-critical injuries and interventions for trapped motor vehicle collision patients: a Delphi study - Tim Nutbeam; Rob Fenwick; Ian Marritt; Brian Lee; Luke Staveley-Wadham; Nigel Lang; Louise Johnson; Nicolas Mattock; Jane Ogilvie; Emily Foote; Francis Screech; Lara Lebeau–Humarau; et al. (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Physically trapped patients following motor vehicle collisions are at high risk of time-critical injuries and poor outcomes. Despite this, there is limited consensus on which injuries should be prioritised and which early interventions are both necessary and feasible in the prehospital setting. This study aims to develop expert consensus on injury categorisation and the delivery of early care interventions to guide clinical and operational decision-making at the scene. Methods A modified Delphi method was used to gather consensus from a multidisciplinary panel of subject matter experts, including clinicians, paramedics, and members of fire and rescue services. In Round 1, participants contributed to the development of draft statements relating to injury time sensitivity, intervention prioritisation, and responder roles. In Rounds 2 and 3, participants rated their level of agreement with these refined statements. A final face-to-face consensus meeting was held to discuss statements that had not yet reached consensus, explore areas of disagreement, and conduct further voting where appropriate. Consensus was defined as ≥ 70% agreement. Results Consensus was achieved on 45 statements across the domains of injury categorisation, time-critical interventions, and multi-agency responsibilities. Participants strongly endorsed the early delivery of analgesia, tranexamic acid, and protection from environmental stressors, regardless of provider background, provided that appropriate training and governance are in place. There was broad support for expanding the scope of practice of non-clinical responders to meet urgent patient needs. Conclusions This Delphi consensus provides a framework for prioritising early interventions in the care of trapped patients. It supports a patient-centred, capability-based approach to prehospital care, emphasising feasibility, urgency, and ethical responsibility. Findings should inform the development of standard operating procedures, triage tools, and training frameworks across emergency services, with further research needed to validate assessment heuristics and address barriers to implementation.